Miliary Tuberculosis in Immunocompromised Patient Induced by Imatinib and Steroid - Fermada, Randa; Fauzar, Fauzar; Kurniati, Roza; Wahid, Irza (Faculty of Medicine, Universitas Andalas, 2021)
Miliary tuberculosis occurs due to the hematogenous spread of Mycobacterium Tuberculosis from the primary complex. The use of steroid and cytotoxic drugs increases the incidence of miliary tuberculosis. Typical manifestations of miliary tuberculosis is snowstorm appearance seen on chest x-ray and evidence of tuberculosis microorganism from the microbiological examination. It has been reported a 33 years old male patient was admitted to the hospital due to breathlessness, chronic coughing, fever, anorexia, weight loss and night sweating with a